Analysis of the Relationship Between Stock Price Index and Exchange Rate in Indonesia (Emerging Market) and in Singapore (Developed Market) using Vector Error Correction Model (VECM) Analysis - Andi Juanna; Umin Kango; Tineke Wolok (International Journal on Economics, Finance and Sustainable Development, 2022)
The COVID-19 pandemic is a problem that occurs in all countries, both developed and developing countries. The impact of this pandemic is not only in the health and social fields, but also the most visible is the economic impact. Restructuring the economy requires investment, both domestic and international. The increase that occurs will make the domestic currency appreciate. Conversely, if there is a downward trend in stock prices, it will cause investors' real wealth to decrease, thereby causing a decrease in the demand for money. A decrease in the demand for money will result in a decrease in interest rates which will have an impact on foreign investment (capital inflow) and ultimately lead to a depreciation of the domestic currency. This study aims to examine the long-term relationship between stock prices (closing price) and the exchange rate in Indonesia as an emerging market and Singapore as a developed market.